2020
DOI: 10.1007/s10533-020-00671-w
|View full text |Cite
|
Sign up to set email alerts
|

Natural atmospheric deposition of molybdenum: a global model and implications for tropical forests

Abstract: Molybdenum (Mo) is an essential trace metal that plays a central role in biological nitrogen fixation (BNF) as the cofactor in the conventional form of the nitrogenase enzyme. The low availability of Mo in soils often constrains BNF in many terrestrial ecosystems. Atmospheric sources may supply a critical source of exogenous Mo to regions with highly weathered soils likely low in Mo, particularly in tropical forests where BNF is thought to be high. Here, we present results of a global model of Mo deposition th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 87 publications
(137 reference statements)
3
20
0
Order By: Relevance
“…Terrestrial regions where Mo limitation have been found, which include several temperate, tropical, and boreal ecosystems (Dynarski & Houlton, 2018; Wong et al., 2020b; and references therein), may be particularly sensitive to anthropogenic Mo inputs. Other regions that may be similarly sensitive to anthropogenic perturbations of the Mo cycle are regions where N limitation is strong and new inputs of Mo from weathering or natural atmospheric deposition are low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terrestrial regions where Mo limitation have been found, which include several temperate, tropical, and boreal ecosystems (Dynarski & Houlton, 2018; Wong et al., 2020b; and references therein), may be particularly sensitive to anthropogenic Mo inputs. Other regions that may be similarly sensitive to anthropogenic perturbations of the Mo cycle are regions where N limitation is strong and new inputs of Mo from weathering or natural atmospheric deposition are low.…”
Section: Discussionmentioning
confidence: 99%
“…Volcanic aerosols can be important local sources from noneruptive volcanoes (Wong et al, 2020b). Eruptive volcanoes could also be important, however, no appropriate long-term data set is available, so we focused on noneruptive emissions using the same approach as Wong et al (2020b) but with CAM6.…”
Section: Volcanoesmentioning
confidence: 99%
“…Together, this suggests that nutrient limitation might be site‐specific, reminiscent of studies carried out in Panama that found both Mo and P and Mo co‐limitation along a soil P and soil Mo gradient (Barron et al., 2009; Wurzburger et al., 2012), but contrast to Central Brazil where no effect of P and Mo addition was found on soil BNF (Wong, Neill, et al., 2020). It is noteworthy that Panamanian and Brazilian soils in these studies had lower (0.3–0.9 and 0.09 ppm, respectively) total soil Mo than the soils here in French Guiana (Table 1), a discrepancy that among other reasons could be linked to the influence of transatlantic atmospheric mineral dust transported from the North African Bodélé Depression (Wong, Mahowald, et al., 2020).…”
Section: Discussionmentioning
confidence: 67%
“…While high rates of BNF are commonly reported for tropical forests (Cleveland et al 1999, Sullivan et al 2014), most studies have been conducted in regions that receive substantial inputs of molybdenum (Mo) from atmospheric dust and sea salt (Wong et al 2020 a ), and inputs of P from dust (Mahowald et al 2008). Even in regions that receive relatively high atmospheric inputs of Mo, low biological availability of Mo may still constrain free‐living BNF.…”
Section: Introductionmentioning
confidence: 99%
“…The southeastern Amazon is a region where Mo and P limitation may be pronounced because soils are developed from old, stable surfaces with little to no parent material contribution (Quesada et al 2011) and where atmospheric inputs are very low (Mahowald et al 2008, Wong et al 2020 a ). While a handful of studies have assessed the simultaneous effects of Mo and P on free‐living BNF rates in the tropics, such as in Hawaii, Panama, Costa Rica, and Belize (Vitousek and Hobbie 2000, Barron et al 2009, Wurzburger et al 2012, Reed et al 2013, Winbourne et al 2017, Stanton et al 2019), these regions have higher weathering and atmospheric inputs, particularly from sea‐salt aerosols (Wong et al 2020 a ). In addition, these studies have either been short‐term experiments testing the addition of Mo and or P, or longer‐term studies with Mo added as a nutrient “cocktail” where responses to Mo alone have not been examined (Vitousek and Hobbie 2000, Barron et al 2009).…”
Section: Introductionmentioning
confidence: 99%